Complete chloroplast genome sequence of Caryocar brasiliense Camb. (Caryocaraceae) and comparative analysis brings new insights into the plastome evolution of Malpighiales - Rhewter Nunes; Ueric José Borges de Souza; Cintia Pelegrineti Targueta; Rafael Barbosa Pinto; Thannya Nascimento Soares; José Alexandre Felizola Diniz-Filho; Mariana Pires de Campos Telles (Genetics and Molecular Biology)
Abstract Caryocar brasiliense (Caryocaraceae) is a Neotropical tree species widely distributed in Brazilian Savannas. This species is very popular in central Brazil mainly by the use of its fruits in the local cuisine, and indeed it is one of the candidates, among Brazilian native plants, for fast track incorporation into cropping systems. Here we sequenced the complete chloroplast genome of C. brasiliense and used the data to access its genomic resources using high-throughput sequencing. The chloroplast exhibits a genome length of 165,793 bp and the typical angiosperm quadripartite structure with two copies of an inverted repeat sequence (IRa and IRb) of 34,902 bp each, separating a small single copy (SSC) region of 11,852 bp and a large single copy (LSC) region of 84,137 bp. The annotation analysis identified 136 genes being 87 protein-coding, eight rRNA and 37 tRNA genes. We identified 49 repetitive DNA elements and 85 microsatellites. A bayesian phylogenetic analysis helped to understand previously unresolved relationships in Malpighiales, placing Caryocaraceae as a separated group in the order, with high supported nodes. This study synthetizes valuable information for further studies allowing a better understanding of evolutionary patterns in the group and providing resources for future breeding programs.